2009
DOI: 10.1158/1055-9965.epi-08-1178
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Circulating Tumor Cells in Peripheral Blood of Patients with Renal Cell Carcinoma Correlates with Prognosis

Abstract: Purpose: The aim of this study was to evaluate the clinical relevance of the presence of disseminated tumor cells in peripheral blood (so-called circulating tumor cells) for renal cell carcinoma patients. Methods: Two hundred thirty-three peripheral blood samples from 154 renal cell carcinoma patients were investigated for the presence of disseminated tumor cells by autoMACS technique and immunocytochemical staining of cytokeratin. The frequency of circulating tumor cells was analyzed statistically for correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 28 publications
(38 reference statements)
1
51
1
Order By: Relevance
“…Moreover, detection of cytokeratin 8/18-expressing CTCs in peripheral blood correlated with poor OS in a study of 154 patients with RCC (P ¼ 0.048; ref. 77). Further studies are required to fully understand the potential of these markers as predictive and prognostic biomarkers in RCC.…”
Section: Discussion and Implications For Therapymentioning
confidence: 99%
“…Moreover, detection of cytokeratin 8/18-expressing CTCs in peripheral blood correlated with poor OS in a study of 154 patients with RCC (P ¼ 0.048; ref. 77). Further studies are required to fully understand the potential of these markers as predictive and prognostic biomarkers in RCC.…”
Section: Discussion and Implications For Therapymentioning
confidence: 99%
“…The spread of neoplastic cells from primary tumor to distant sites is a crucial step in the metastasis process and, thus, the detection of CTCs may provide evidence about disease aggression. Bluemke and colleagues screened the status of CTCs in the blood samples from renal carcinoma patients and revealed that the presence of CTCs correlated with the lymph node status and synchronous metastasis (9). The ability to detect CTCs by analyzing the expression of CA9 as a tumor-specific biomarker in blood samples has previously been reported (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…B7-H1, a cell surface glycoprotein that participates in T-cell costimulation, is a another marker of interest that was independently correlated with a greater risk for RCC death [59]. Finally, an intriguing study by Bluemke et al [60] correlated the presence of circulating tumor cells and lymph node positivity, distant metastases, and the risk for tumor-related death. Other studies evaluating the significance of circulating endothelial cells and circulating tumor enzymes are under way [61,62].…”
Section: Prognostication/predicting Response To Therapymentioning
confidence: 99%